2019
DOI: 10.1016/j.heliyon.2019.e02646
|View full text |Cite
|
Sign up to set email alerts
|

Ecologically relevant arsenic exposure alters female mate preference and anxiety-like behavior in Betta splendens

Abstract: Arsenic is a metalloid pollutant that is commonly found in surface and groundwater worldwide. Toxicological effects of arsenic are relatively well-known, but much less studied are its effects on behavioral endpoints, which may have considerable evolutionary and population-level consequences. Here we investigated the effects of exposure to environmentally relevant concentrations of arsenic (0, 10 and 100 μg/L) for 96-hours on female preference for male color (i.e. red versus blue) in Betta splendens, an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 52 publications
0
1
1
Order By: Relevance
“…In the scototaxis task, we found a significant preference for the black side. This differs from a previous study that found no preference [39], though the study was only conducted in females. Further exploration of sex differences and correlations with other anxiety measures is a useful next step for this species.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the scototaxis task, we found a significant preference for the black side. This differs from a previous study that found no preference [39], though the study was only conducted in females. Further exploration of sex differences and correlations with other anxiety measures is a useful next step for this species.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous literature has conducted an open field task [37,38], a scototaxis task [39], and a mirror task [23,24,[40][41][42][43] in Betta splendens. Researchers have also uncovered a behavioral syndrome in Betta by correlating behavior across multiple assessments of boldness and aggression [44].…”
Section: Introductionmentioning
confidence: 99%